Finding God in All Things through Poetry - Novita Dewi (Journal of Language and Literature, 2021)
Poetry is a language of devotion. It is the melody that resonates from one’s pure conscience. Being the most important and richest part of our spiritual practice, people read and write poems to help them gain understanding about themselves, each other, and the world around them. Examining world poetry, mainly from America, Indonesia, and Sri Lanka which  tell about the presence of God, this article attempts to find out how God the Creator is present and represented, focusing as it does on the connection between poetry and spiritual exercises. Each of the seven poems under discussion is read by considering Ignatian Spirituality of which the core is “Finding God in All Things”. The selected poems show that God can indeed be found in three main spots. First, God resides in the universe. The presence of God in nature is a common theme shared by the poets discussed. Second, the speakers of the poems find God within themselves. They find God through discretion. Third, some of them find the face of God in that of other people because humans are created in His image. The poems open an awareness that God is present in the sufferings of others. In conclusion, poetry serves as both prayers and spiritual exercises that can improve people’s inner compassion and justice.